PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MELALUI STRATEGI TTW DALAM PEMBELAJARAN KOOPERATIF PADA MATERI HIMPUNAN DI KELAS VII - Maria Celes Rajagukguk; Nahor Murani Hutapea; Sakur Sakur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to produce mathematic learning device in the form of lesson plan and student worksheet using TTW strategy in cooperative learning on the subject of SET for VII grade students. The study model used is 4-D that consist of define, design, develop, and desseminate. The research instrument used is validity device and practicality device. The validity device is a validation sheet to assess the feasibility of lesson plans and student worksheet. The practicality device is in the form of observation sheet of learning process implementation and questionnaire of student response. Learning device developed are validated by three validators. The research trials were is tested in a small group were conducted in SMP Negeri 21 Pekanbaru and large group in SMP Negeri 20 Pekanbaru. Small group trial aims to assess the practicability based on student response questionnaire, while the large group to assess the practicability based on the open questionnaire sheet of learning process implementation and student response questionnaire. Based on the data analysis, it can be conclude that the average value for lesson plan is 3.70 in very valid category which means that lesson plan is feasible to be used and as well as the average value for student worksheet are 3.95, that are in very valid category which means that student worksheet are feasible to be tested. The average percentage of student worksheet valued as very practical with mean score for small group and large group testing are 95.60% and 93.82%. These categories mean that the lesson plan and student worksheet are feasible to used in school.Key words: Mathematics Learning Device, TTW Strategy, Cooperative Learning, Development Research, 4-D Model